2010
DOI: 10.3233/nre-2010-0577
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers' support needs after brain injury: A synthesis of perspectives from caregivers, programs, and researchers

Abstract: There is a dearth of support for family members who assume caregiving responsibilities following acquired brain injury (ABI). This qualitative study broadens the understanding of ABI caregiver support needs through data triangulation from multiple interview sources across different settings. Thirty-nine caregivers across urban and rural settings in Ontario participated in focus groups. Interviews focused on ABI support services received, their utility, access barriers, needed supports, and suggestions for serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 32 publications
4
76
0
Order By: Relevance
“…Geographical distance created both practical and personal barriers to accessing service needs, including financial, transport, lack of time, fatigue and feelings of isolation. These issues have been reported elsewhere (Gan, Gargaro, Brandys, Gerber, & Boschen, 2010;Tong et al, 2013), and all affected the mothers' physical and emotional well-being (Hoogsteen & Woodgate, 2013).…”
Section: Discussionmentioning
confidence: 83%
“…Geographical distance created both practical and personal barriers to accessing service needs, including financial, transport, lack of time, fatigue and feelings of isolation. These issues have been reported elsewhere (Gan, Gargaro, Brandys, Gerber, & Boschen, 2010;Tong et al, 2013), and all affected the mothers' physical and emotional well-being (Hoogsteen & Woodgate, 2013).…”
Section: Discussionmentioning
confidence: 83%
“…Several studies have found that caring for an individual who has sustained a TBI involves many challenges (Arango-Lasprilla et al 2010; Ergh et al 2002; Gan et al 2010; Jumisko et al 2007; Lefebvre et al 2008). Most studies on this topic focus on caregiving experiences from six months to several years post–injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on family caregivers in the context of traumatic brain injuries (TBIs) (Arango-Lasprilla et al 2010; Gan et al 2010; Livingston et al 2010; Phelan et al 2011; Vangel, Rapport & Hanks 2011). Traumatic brain injuries (TBI) are regarded as a global public health problem, with research showing that TBIs affect an estimated 10 million people worldwide every year (Hyder et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further rehabilitation support during the post-acute stages of recovery, such as home assessments or on-going therapy maintenance, would also be optimal. Gan et al (2010) examined the support needs after brain injury and made several recommendations for support services. They suggested that family systems-based services should be accessible, life-long, individualized and flexible, as well as efficient, and that support system-based services should include proper diagnoses, incorporate a multi-component approach, provide brain-injury-specific services that are responsive to needs with proactive follow-ups, and importantly, provide continuous education.…”
Section: Discussionmentioning
confidence: 99%